PERAN DAN POTENSI KYAI PESANTREN DALAM PENGEMBANGAN LEMBAGA KEUANGAN SYARIAH DI PEKALONGAN Tinjauan WoM Marketing dan Buzz Marketing - AM. M. Hafidz MS; A. Tubagussurur; Marlina (JURNAL PENELITIAN, 2014)
Because of their strength, charisma, knowledge, authority in the boarding school, influential leverage, expertise, and social networks, Kyai Pesantren have the potential to market Islamic Financial Institutions by creating buzz and word-of-mouth (WoM) marketing. Their role as marketers could include: (1) providing education and learning on Islamic economics, Islamic financial institutions, and fiqh muamalah; (2) building several business units to teach their students operational and practical aspects of Islamic economics; (3) serving as members of the Sharia Supervisory Board in existing Islamic financial institutions as guardians of Sharia compliance; and (4) disseminating information about the role of Islamic financial institutions to the community when delivering lectures.